ANALISIS PROFITABILITAS, EARNING PER SHARE, PERTUMBUHAN PENJUALAN SEBELUM DAN SESUDAH BERSERTIFIKAT ISO - Anjelina, Erlina; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the difference among Profitability, Earnings per Share, and Sales Growth before and after the companies are certified by ISO 9001-2008 in 2009 and 2010. The samples are 20 manufacturing companies which have been selected by using purposive sampling and these manufacturing companies have issued their financial statements and these statements have been obtained from the official websites of Indonesia Stock Exchange i.e. (www.idx.co.id). The period of the research is two years before and two years after the companies are certified by ISO 9001-2008 in 2007-2012 periods. The data analysis technique has been done by using statistic analysis technique and SPSS (Statistical Package for Social Sciences) version 20 and it uses more than one independent variables i.e.: profitability, earnings per share, and sales growth. Profitability variables are Net Profit Margin, Return on Asset, and Return on Equity. The result of the research shows that 3 variables have different condition before and after the companies are certified by ISO 9001-2008 i.e. Net Profit Margin, Return on Asset, and Earnings per Share whereas the remaining 2 variables do not have any different condition before and after the companies are certified by ISO 9001-2008 i.e. Return on Equity and Sales Growth.Keywords: ISO 9001 â 2008 Certificate, Profitability, Sales Growth